Pendampingan Masyarakat dalam Mengembangkan Tradisi Manganan sebagai Wujud Integrasi Nilai-Nilai Islam dan Kearifan Lokal di Desa Sembung ParenganTuban - Zeni Faridah; Ahmad Ainur Rizqi, M; Abdul Hamid (Journal of Innovation and Contribution to Community Service, 2025)
This study examines community empowerment by integrating Islamic values into the local wisdom of the Manganan tradition in Sembung Village, Parengan, Tuban. The Manganan tradition, a long-standing cultural practice rooted in communal togetherness and gratitude, has become an effective means of strengthening social cohesion and fostering religious awareness. Using the Participatory Action Research (PAR) method, this research highlights how Islamic teachings are embedded in the rituals, symbols, and communal activities of Manganan, transforming it into a platform for moral education, spiritual development, and community solidarity. The findings show that integrating Islamic values with local traditions not only preserves cultural heritage but also fosters active community participation, cooperation (gotong royong), and the internalization of religious values in daily life. This synergy between religion and culture contributes significantly to sustainable community development and the revitalization of local identity